Barriers and facilitators related to self-management of shoulder pain: a systematic review and qualitative synthesis. (November 2022) - O'Shea, Aidan; Drennan, Jonathan; Littlewood, Chris; Slater, Helen; Sim, Julius; McVeigh, Joseph G.
Objective: The objective of this review was to identify barriers and facilitators related to self-management from the perspectives of people with shoulder pain and clinicians involved in their care. Data sources: CINAHL, MEDLINE, PsycINFO, SPORTDiscus, Embase, ProQuest Health, Web of Science, and Scopus were searched from inception to March 2022. Review methods: A meta-aggregative approach to the synthesis of qualitative evidence was used. Two independent reviewers identified eligible articles, extracted the data, and conducted a critical appraisal. Two reviewers independently identified and developed categories, with validation by two further researchers. Categories were discussed among the wider research team and a comprehensive set of synthesized findings was derived. Results: Twenty studies were included. From the perspective of patients, three synthesized findings were identified that influenced self-management: (1) support for self-management, including subthemes related to patient-centred support, knowledge, time, access to equipment, and patient digital literacy; (2) personal factors, including patient beliefs, patient expectations, patient motivation, pain, and therapeutic response; and (3) external factors, including influence of the clinician and therapeutic approach. From the perspective of clinicians, two synthesized findings were identified that influenced self-management: (1) support for self-management, including education, patient-centred support, patient empowerment, time, and clinician digital literacy; and (2) preferred management approach, including clinician beliefs, expectations, motivation, therapeutic approach, and therapeutic response. Conclusion: The key barriers and facilitators were patient-centred support, patient beliefs, clinician beliefs, pain, and therapeutic response. Most of the included studies focused on exercise-based rehabilitation, and therefore might not fully represent barriers and facilitators to broader self-management.